Financial Institutions’ Development and Economic Growth: Evidence from Sri Lanka by Employing ARDL Model - Jathurika Gowthaman (International Journal of Management, Accounting and Economics)
This research aims to analyse the influence of financial institutions' development on the economic growth of Sri Lanka in both the short and long term, to shed light on the significance of financial institutions in stimulating the economic performance of the country. Data for the study is collected solely from Sri Lanka, utilising annual data from 1963 to 2021. Broad Money, Financial system deposits, Domestic credit to the private sector, and Claims in the Private Sector are used to measure financial depth and financial efficiency which are the indicators of financial institutions’ development.  Statistical tools such as Unit Root Tests and Co-Integration Tests are employed using the E-Views version six software package. Findings indicate significant positive short-run and long-run impacts of financial institutions' development on economic growth. Although some variables exhibit insignificant results, Broad Money and Claims in the Private Sector emerge as the most influential factors affecting the economic growth of Sri Lanka. The hypothesis adopted in the study can be accepted that there is a supply-leading hypothesis that exists in terms of financial institutions’ development and economic growth in Sri Lanka. The Central Bank of Sri Lanka can adopt policies to ease the monetary conditions relating to the lending and depositing facilities of financial institutions. This can induce the Broad Money and the Claims on the Private Sector, and it will stimulate the economic growth of the country as a whole. Thus, this paper sheds light on the specific area on which the country should focus to reconstruct the country from the worst.